Program Aplikasi Pendaftaran Online Untuk Pondok Pesantren Modern Daar El Azhar - Gustiyana, Ageng (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Education and learning are two things that are closely related and can not be separated from each other. Both are incredibly important point for the strategic development and the people and the construction of the Islamic community. Then each individual of Muslims in general and educators in particular need to improve education and teaching activities both in quality and quantity. The purpose of making this Online Registration application program is to assist students in registering online. In this thesis, the application program Online Registration For Modern Islamic Schools Daar El Azhar created using PHP programming language and database applications using MY SQL